1990
DOI: 10.1200/jco.1990.8.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted treatment choice in stage I nonseminomatous testicular germ cell cancer by regarding vascular invasion in the primary tumor: a prospective trial.

Abstract: Based on the results of a retrospective study, which found blood vessel invasion to be the most important prognostic factor in clinical stage I nonseminomatous testicular germ cell cancer (NSTGCC I), a prospective study was started in 1985 which assigned NSTGCC I patients without evidence of vascular invasion to surveillance and patients with vascular invasion to two cycles of adjuvant chemotherapy with cisplatin, etoposide, and bleomycin. Twenty-two patients entered the surveillance group and 18 patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 10 publications
0
36
0
3
Order By: Relevance
“…[39][40][41][42][43][44][45][46][47][48] A total of 1768 patients were evaluated and with a median follow-up range of 19.5 to 76 months, 378 recurrences were reported (21.4%). Across the studies, 13 deaths from testicular cancer were reported, along with 7 other deaths.…”
Section: Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43][44][45][46][47][48] A total of 1768 patients were evaluated and with a median follow-up range of 19.5 to 76 months, 378 recurrences were reported (21.4%). Across the studies, 13 deaths from testicular cancer were reported, along with 7 other deaths.…”
Section: Surveillancementioning
confidence: 99%
“…The survival outcomes are summarized in Table 5. 13,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] The presence of microscopic vascular or lymphatic invasion in the primary tumour is the most important factor predicting relapse and the presence or absence of this factor has been used to divide patients: those with high-risk disease (a third of the cases) who have about a 50% risk of relapse, and those with low-risk disease who have about a 15% to 20% risk of relapse. 45 …”
Section: E25mentioning
confidence: 99%
“…Preliminary results show only 1 relapse out of 101 enrolled patients after a median follow-up of less than 2 years. The patient is in marker remission following further chemotherapy [18], These results seem to overcome the fear for the teratoma relapse and the relapse of chemoresistant cancer, as it could have been suggested by the surgical findings [12,13,17], and by the Austrian experience [19]: one teratoma and one uncurable retroperitoneal recurrence of germ cell cancer out of 18 patients with vascular invasion treated with two courses of adjuvant PEB (cisplatin 20 mg/m2, days 1-5; VP-16 100 mg/m2, days 1-5, bleomycin 30 mg/m2, days 2, 9, 16) after a median follow-up of 30 months. Anyway, a longer follow-up and an improved knowledge of risk fac tors [20] willl be necessary to draw definite conclusions.…”
Section: Stage II Seminomamentioning
confidence: 90%
“…Late relapses have been observed in patients with clini cal stage I NSGCT of the testis treated with inguinal orchiectomy and surveillance [10][11][12][13], inguinal orchiecto my and retroperitoneal lymph node irradiation [14,15], and inguinal orchiectomy and adjuvant chemotherapy [16], However, late relapses are particularly uncommon in patients with PSI NSGCT treated with inguinal or chiectomy and RPLND (table 1). Physicians must remain vigilant for such late recurrences since most can be sal vaged with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%